2018
DOI: 10.14202/vetworld.2018.542-548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doublesynch and Estradoublesynch protocols on estrus induction, conception rate, plasma progesterone, protein, and cholesterol profile in anestrus Gir heifers

Abstract: AimThis study aimed to evaluate the efficacy of Doublesynch and Estradoublesynch protocols on estrus induction, conception rates, plasma progesterone, protein, and cholesterol profile in anestrus Gir heifers.Materials and MethodsIn this study, 50 pubertal anestrus Gir heifers were selected from the field and farm conditions. The heifers were dewormed (injection ivermectin, 100 mg, s/c) and supplemented with minerals and vitamins (injection organic phosphorus 800 mg and injection Vitamin AD3E and Biotin 10 ml i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…These findings with respect to values coincided well with the previous reports of Singh et al (2004), Jerome et al (2016) and Prajapati et al (2018). However, other reserchers (Parmar et al, 2012;Chaudhary et al, 2018) reported higher values of total protein than the present findings. Optimum protein level is necessary for the development of endocrine and sex organs.…”
Section: Blood Biochemical Profilesupporting
confidence: 93%
“…These findings with respect to values coincided well with the previous reports of Singh et al (2004), Jerome et al (2016) and Prajapati et al (2018). However, other reserchers (Parmar et al, 2012;Chaudhary et al, 2018) reported higher values of total protein than the present findings. Optimum protein level is necessary for the development of endocrine and sex organs.…”
Section: Blood Biochemical Profilesupporting
confidence: 93%
“…(2013) [1] also reported similar observation in anoestrous Kankrej cows treated with Ovsynch protocol while higher intensity of oestrus (33.33-58.33%) than that of the present investigation was reported by Chaudhari et al (2012) [6] and Nevkar et al (2012) [14] in acyclic crossbred cows treated with Ovsynch protocol. Velladurai et al (2014) [25] recorded the intensity of oestrus as intense, intermediate and weak in 50.00, 37.50 and 12.50 percent cows treated with Ovsynch protocol which was found higher than that recorded in the present investigation.…”
Section: Intensity Of Estrussupporting
confidence: 86%
“…Cholesterol serves as a precursor for the synthesis of progesterone by ovarian luteal cells. In a recent study, significantly higher mean plasma cholesterol concentration was documented in non-conceived than conceived Gir heifers treated with Doublesynch and Estradoublesynch protocols (Chaudhary et al 2018). Moreover, the mean plasma protein levels on the day of FTAI and day 12 post-AI were significantly higher compared to day 0 and 9 of the Estradoublesynch protocol.…”
Section: Resultsmentioning
confidence: 89%